2011
DOI: 10.1093/humrep/der269
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal contraception and mental health: results of a population-based study

Abstract: The influence of hormonal birth control on mental health is modest and mainly favourable. The length of current OC use seems to have some beneficial effects on mood although the longer the duration of use, the greater the association with a diagnosis of alcohol dependence. Knowledge of the use of hormonal contraception might be of value when assessing psychopathology in women. The cross-sectional design, with partly retrospective data collection, precludes any causal conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 40 publications
1
32
0
2
Order By: Relevance
“…The studies took place in seven different countries: United States (10), Australia (5), England (3), Canada (2), France (2), Finland (1), and Russia (1). Nine studies collected data from women in substance abuse treatment (including White et al, 1993 whose population also include needle exchange clients), seven from women using drugs or alcohol but not in drug treatment (including a subset of women from Toffol et al, 2011), and eight from other populations where >50% of the group reported drug and alcohol use (i.e., street-based female sex workers, chronically homeless women, incarcerated women, or women living with HIV or hepatitis C). Of note, fourteen studies included details about the specific type of drug(s) used, with more than half (51%) of the women in these studies reporting opioid use and much smaller percentages, alcohol and cocaine.…”
Section: Resultsmentioning
confidence: 99%
“…The studies took place in seven different countries: United States (10), Australia (5), England (3), Canada (2), France (2), Finland (1), and Russia (1). Nine studies collected data from women in substance abuse treatment (including White et al, 1993 whose population also include needle exchange clients), seven from women using drugs or alcohol but not in drug treatment (including a subset of women from Toffol et al, 2011), and eight from other populations where >50% of the group reported drug and alcohol use (i.e., street-based female sex workers, chronically homeless women, incarcerated women, or women living with HIV or hepatitis C). Of note, fourteen studies included details about the specific type of drug(s) used, with more than half (51%) of the women in these studies reporting opioid use and much smaller percentages, alcohol and cocaine.…”
Section: Resultsmentioning
confidence: 99%
“…Cheslack-Postava, for example, found OCPs to be either unassociated with or protective against multiple sub-threshold mood disorders [23]. A 2011 study of Finnish women found that OCP use modestly protected against most psychiatric disorders [25]. A 2013 study using data from the National Longitudinal Study of Adolescent Health found that OCP use protected against depressive symptoms among US women ages 25–34 [24].…”
Section: Discussionmentioning
confidence: 99%
“…For one, women with long-term alcohol problems may have decided early on to limit childbearing in a reliable manner, as other studies have posited. 39 Second, women with those histories may also be connected to a network of social services (e.g., drug and alcohol treatment) that may indirectly affect access to other types of health services, including family planning. Other investigators have shown, for example, positive associations between several types of substance use with access to sexual and reproductive healthcare.…”
Section: Discussionmentioning
confidence: 99%